The Controversy of the 2013 Severe Water Disruptions in Selangor, Malaysia: A Critical Analysis - Hamirdin Ithnin; Mujirah Mokmin; Nordin Sakke (Penerbit UPSI, 2014)
The state of Selangor is the most developed state in Malaysia, as such the capability of its water supply system is always on the heel in trying to meet the ever-growing demand. The government of the state prior to the 2008 General Election had embarked on an interbasin water transfer project with the aim of boosting the availability of raw water for treatment and subsequently to supply the state with a projected future demand curve. A change in government in 2008 saw a change in emphasis with regard to the water supply system. The present state government is of the view that the interstate water transfer project ought to carry out concurrently with the restructuring of the water supply system of the state. Other parties such as the concessionaires are on an opposite view. As such there was a stalemate regarding the progress of the interstate water transfer and the restructuring of the water supply system. It looked as if the party which wanted to go ahead with the water transfer project hatched the idea that water crisis was imminent in the state. The irony was that when the horn was blown to drum up water crisis issue in the state, it rained, and dams in the state were overflowing. The present state government was more inclined to keep water tariff at its present level, and at the same time urge the concessionaires to commit themselves to the pledge of reducing NRW, which it believes if kept low, can compensate for the increase in demand. As such, a settlement is not in sight yet, but with the backing of the Federal Government, the interstate water transfer project continued, at the same time the restructuring of the water supply system in the state remains a stalemate. This paper analyzes the issue from a non-partisan view.